A Survey of Genome Compression Methodology - Roy, Subhankar; Mitra, Rituparna (International Journal of Computer Sciences and Engineering, 2025)
Storing the information about human nucleotide is become essential now a day for various medical research purposes. A human genome consists of almost 3.2 billion nucleotides. It is unmanageable to store, access and retrieve the desired information from the massive bulk of unprocessed data. So the possible solution is genome compression. By compression we mean that we are restricting on the data storage. Existing data compression methodology is not suitable to deal with this massive data. In this paper we provide a survey analysis on various types of genome compression and read compression algorithm which are specially designed to handle this voluminous raw DNA information. To extract the unique non repeated information from the whole sequence is actually a tough challenge .These compression algorithms not only save time but also provide high compression rate. We have discussed all the types of compression algorithm with their distinctive approach. Each of them having some benefit over other. We also briefly discuss on various file formats used while compression